Pengaruh Pengetahuan Produk, Kebutuhan dan Promosi Terhadap Keputusan Nasabah Menggunakan Produk Murabahah Mikro Di BPRS Mitra Mentari Sejahtera Ponorogo - Alfikaromah, Lia; Nurhidayati, Maulida (JPSDa: Jurnal Perbankan Syariah Darussalam, 2023)
BPR Syariah Mitra Mentari Sejahtera is a company engaged in the field of Islamic banking that serves deposits in the form of savings and time deposits and distributes sharia-managed financing located in Ponorogo Regency. One of the financing products available at BPRS Mitra Mentari Sejahtera Ponorogo is a micro murabaha product. Based on the data obtained, it is known that during the last two years, micro muarabahah financing products have not experienced an increase in the number of customers. According to Philip Kotler and Kelvin Lane Keller, there are several factors that influence customer decisions such as knowledge, needs and according to Mansur Razak, one of the factors that influence decisions is promotion. The purpose of this research is to examine and analyze the effect of knowledge of financing products, needs and promotions on customer decisions. using micro murabahah products at BPRS Mitra Mentari Sejahtera Ponorogo. The research method used in this study is a quantitative method with a population of 299 and a sample of 75 respondents. The data collection technique for this study was to distribute questionnaires to 75 micro murabaha financing customers. The data analysis technique was carried out using multiple linear regression methods. In this study, the knowledge variable has no effect on customer decisions, while the need and promotion variables have an effect on customer decisions. But simultaneously all variables influence the customer's decision to use micro murabahah products.